The problem of literary relationship between Ilia Chavchavadze and Grigol Orbeliani in the thought of Simon Chikovani - Sumbadze, Tea (Actual Problems of Kartvelology, 2019)
One of the important part of the famous Georgian poet Simon Chikovani's literary heritage is the essayist letters, which refer to the works of classics of Georgian poetry. The present article analyzes Simon Chikovani's views on Ilia Chavchavadze's poetry. The main issue discussed here is “Ilia Chavchavadze and Grigol Orbeliani”. S. Chikovani argues with relevant examples that the influence of Grigol Orbeliani was evident in Ilia Chavchavadze's poetry in the early years. However, this proximity is external and their poetic beliefs are mostly contradictory. Simon Chikovani analyzes the influence of folk poetry in the works of Ilia Chavchavadze and Grigol Orbeliani, as well as he talks about the use of archaic forms in the creation of these two lyricists.